Adlayers of Alkanedithiols on Au(111): effect of disulfide reducing agent - Cometto, Fernando Pablo (2013)
High-resolution photoemission spectroscopy is used to characterize adlayers of ethane-, hexane-, and nonanedithiol molecules grown on Au(111) surfaces by the immersion method. The effect of using a reducing agent during and after the immersion to inhibit or eliminate S–S bonds is investigated. Our results demonstrate that immersion 24 h in millimolar dithiol ethanolic solutions gives rise to the formation of multilayers; this effect is more pronounced in the case of ethanedithiol, the shortest molecule. A post-treatment with a disulfide reducing agent is effective to produce monolayers of standing-up molecules; this effect is again more pronounced in the case of ethanedithiol. Finally, the immersion 24 h in a solution containing dithiol and the reducing agent gives an unexpected result: most molecules remain adsorbed in the lying-down configuration; in this case, the almost complete suppression of the standing-up phase occurs equally with the three types of molecules, which suggests that the formation of S–S bonds must be important for the lifting of the molecules.